Marketing Management in Agribusiness: Branding Strategies and Market Penetration - Wijayanthi, Ida Ayu Trisna; Setiyarti, Tettie; Karwini, Ni Ketut; Handayani, Ni Wayan Ana Rahita (PT. Anagata Sembagi Education, 2025)
This study aims to analyze marketing strategies, particularly branding and market penetration, employed by agribusiness actors in Indonesia. In the context of agribusiness, branding not only serves to enhance product image but also to create an emotional connection with consumers. This research uses a qualitative approach through in-depth interviews with agribusiness entrepreneurs in the horticulture, processed food, and organic product sectors. The results show that agribusiness actors with better educational backgrounds and experience are more capable of implementing modern marketing strategies, including branding and digital marketing. However, micro and small enterprises still face challenges in adopting digital marketing technologies. This study also reveals the importance of collaboration with communities and the use of social media as effective marketing channels. These findings provide insights into the challenges and opportunities faced by agribusiness actors in building a strong brand and achieving broad market penetration.